Immunolipid magnetic bead-based circulating tumor cell sorting: a novel approach for pathological staging of colorectal cancer - Deng, Qingyan; Li, Weidong; Huang, Yueming; Wang, Haitao; Zhou, Xinhao; Guan, Zhifen; Cheng, Bohao; Wang, Yao (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to assess whether circulating tumor cells (CTCs) from colorectal cancer (CRC) could be used as an alternative to tissue samples for genetic mutation testing, overcoming the challenge of difficult tumor tissue acquisition.MethodsWe developed an immunolipid magnetic bead (IMB) system modified with antibodies against epithelial cell adhesion molecule (EpCAM) and vimentin to efficiently separate CTCs. We prepared EpCAM-modified IMBs (Ep-IMBs) and vimentin-modified IMBs (Vi-IMBs). The separation efficiency of the system was evaluated via in vitro experiments and by capturing and counting CTCs in blood samples from 23 CRC patients and 20 healthy controls. Hotspot mutations in patient tissue samples were identified via next-generation sequencing (NGS), whereas mutations in blood CTCs were detected via Sanger sequencing. The concordance between hotspot mutations in tumor tissue and blood CTCs was analyzed.ResultsThe CTC sorting system exhibited good dispersion, stability, and low cytotoxicity, with a specificity of 90.54% and a sensitivity of 89.07%. CRC patients had an average of 8.39 CTCs per 7.5 mL of blood, whereas healthy controls had 0.09 per 7.5 mL of blood. The consistency of gene mutations was as follows: TP53 (91.31%), PIK3CA (76.00%), KRAS (85.36%), BRAF (51.00%), APC (65.67%), and EGFR (74.00%), with an overall gene mutation consistency of 85.06%.ConclusionOur CTC sorting system, which is based on Ep-IMBs and Vi-IMBs, effectively captures CTCs in the peripheral blood of CRC patients and enables clinical hotspot gene mutation testing via these enriched CTCs. This system partially solves the problem of difficult tumor tissue sample collection and provides a reference for gene mutation testing in early diagnosis, therapeutic efficacy evaluation, prognosis assessment, and minimal metastasis detection in CRC patients, showing significant potential for clinical application, especially in targeted therapy gene testing for CRC.